Strategi Pemasaran melalui Platform Digital serta Diversifikasi Produk Beras Kelompok Tani Ngudi Makmur untuk meningkatkan daya saing di era digital - Sari, Eka Anisa; Sirajuddin, Muhammad Mar'ie; Hafni, Diska Arliena; Tribuwana, Mohammad Endy; Kamal, Refal Mustafa; Puspita, Amanda Dela; Khoirunissa, Khoirunissa; Erviana, Vera Yuli (Universitas Muhammadiyah Magelang, 2025)
This community service activity aims to increase the capacity of the Ngudi Makmur farmer group in Seyegan, Sleman, Yogyakarta through digital marketing training and rice product diversification. The training materials covered digital marketing, branding, communication, and rice flour processing. The methods used included counseling, interactive training, and evaluation through pre- and post-tests. The evaluation results showed an increase in the average score of participants from 0.57 in the pre-test to 0.89 in the post-test. The level of understanding of participants before the training was still low, especially in the aspects of communication (15 participants) and rice product diversification (10 participants). After the training, there was a significant and even increase in all aspects, namely digital marketing (33 participants), branding (35 participants), communication (29 participants), and rice product diversification (27 participants). Thus, this activity has proven effective in increasing the knowledge and skills of farmer groups, both in utilizing digital platforms for marketing and in developing innovative rice-based products. This program is expected to strengthen the competitiveness and economic independence of farmer groups in a sustainable manner.